Qualidade e potencial energético da madeira de desbaste de mogno africano - Moraes, Mariana Dianese Alves de (2017)
Knowledge of the quality and energy potential of african mahogany wood is essential for its proper use. The objective of this work was to evaluate the anatomical characteristics, basic density and energy potential of the wood of Khaya ivorensis (A. Chev) obtained from the thinning of a commercial plantation at the age of seven years. Five medium trees cut during thinning were selected and two wooden discs were cut in different longitudinal positions (0, DAP, 25, 50, 75 and 100% of the commercial height; minimum diameter of 6 cm): (i) one disc of each (Density, immediate chemical, higher calorific value and energy density), and the density and density of the vessels, (Density, energetic strength and energy density) were used to compose a sample of all longitudinal positions for the characterization of biomass, Durability, volumetric expansion and tensile strength by diametrical compression). For the production of charcoal, wedges of wood of discs of the height of the DAP (1.3 meters) were used, being carbonized in muffle furnace for the later characterization (basic and energetic density, immediate chemical, higher calorific value and gravimetric yield). The evaluations of the basic density and the anatomical characteristics of the wood of K. ivorensis at the age of 7, from thinning, showed that the exchange meristem is forming until this period the so-called juvenile wood, not being indicated for the solid uses such as furniture and floors. The models of the longitudinal profiles of the basic density of the wood were similar for all the trees, characterized by the decrease of the base to the intermediate portion, with increase to the apex of the trunk. For the length of the fibers the values did not present a model of common longitudinal variation along the trunk of the trees. The width, lumen diameter and wall thickness of the fibers presented a variation model characterized by lower values at the base of the trunk, followed by decreasing-stabilization of the values up to the top of the trunk. The characteristics of biomass and charcoal indicated lower quality parameters for energy use. Biomass carbonization promoted the reduction of basic density and volatile materials and the increase of fixed carbon, ash, higher calorific value and energy density. The compaction of the biomass improved its energetic and physical characteristics, being the indicated form for the energetic use of the juvenile wood of K. ivorensis, obtained in the thinning of the commercial plantation.